Peran Mediasi Job Satisfaction Terhadap Turnover Intention : Pengaruh Person Organization Fit, Komitmen Organisasi, dan Work Engagement - Santi Suciningtyas; Tri Handayani; Prasasti Indira Wardani (Publikasi Indonesia, 2022)
This study aims to determine and analyze the influence of Person Organization Fit, Organizational Commitment, and Work Engagement on Turnover Intention. In addition, it is also to find out and analyze whether Job Satisfaction can mediate its free variables. While the number of samples used as many as 105 respondents. The sampling technique used was the accidental sampling technique. The test equipment used to test the research instrument is in the form of validity test, reliability test. The data analysis technique uses the Goodnees of fit, normality, outlier and mahalanobis distance methods. Hypothesis testing was carried out using direct effects and indirect effects. The results showed that the variable person organization fit had a significant effect on turnover intention of employees of PT. Daiwabo Garment Indonesia. The organizational commitment variable has a significant effect on turnover intention in employees of PT. Daiwabo Garment Indonesia. Work engagement variable has no significant effect on turnover intention of employees of PT. Daiwabo Garment Indonesia. Job satisfaction variable has a significant effect on turnover intention of employees of PT. Daiwabo Garment Indonesia. Person organization fit variable has a significant effect on turnover intention mediated by job satisfaction on employees of PT. Daiwabo Garment Indonesia. The organizational commitment variable has a significant effect on turnover intention mediated by job satisfaction on employees of PT. Daiwabo Garment Indonesia. The work engagement variable has a significant effect on turnover intention mediated by job satisfaction on employees of PT. Daiwabo Garment Indonesia.